E-Commerce Delivery Order System Based On ISO 9126 Model In Jeddah, Saudi Arabia - Siswanto Siswanto; H. Riefky Sungkar (IAES Indonesia Section, 2019)
The limited mobility of Muslim women in the city of Jeddah who must be accompanied by their Muslim family or husband or with fellow Muslim female friends, if they want to leave the house to shop or entrepreneurship has become a culture in the country of Saudi Arabia. The research objective was to create a prototype e-commerce delivery order system for Muslim women in the city of Jeddah. The development of an ecommerce delivery order system uses a prototype method, and tests the quality of variables with the ISO 9126 model. The result of testing of the application variables for functionality, reliability, efficiency and user usability is 77.3%.